Francie Yob - Oral History, WWII - Interview - Service Organization for Youth (Raton, New Mexico SOY, 2001)
Locally produced video of, oral history of the area (Raton) primarily during WWII.
Keywords: Francie Yob; WWII Stories -- Raton, NM; Joseph Frank Pobar